Hubungan Pengetahuan, Sikap dan Perilaku Terhadap Personal Hygiene Penjamah Makanan (Food Handler) Di Pasar Retail Jakabaring Palembang: Hubungan Pengetahuan, Sikap dan Perilaku Terhadap Personal Hygiene Penjamah Makanan (Food Handler) Di Pasar Retail Jakabaring Palembang - Nurafni Maftukhah (IKesT Muhammadiyah Palembang, 2024)
Background: Personal Hygiene is a health effort by maintaining and protecting individual cleanliness to realize proper Personal Hygiene in food handling. Objectives: To determine the relationship between knowledge, attitudes and behavior towards personal hygiene of food handlers in the Jakabaring retail market Palembang. Method: Using Descriptive Analytics with a Cross Sectional Approach with a sample of 30 respondents. Results: Based on statistical tests with the Chi Square test, the p value is ≥ 0,05 (0,201) so That Ha is rejected, meaning there is no relationship between Knowledge and Personal Hygiene. The results of statistical tests with the chi square test show a p value of ≤ 0,001 ) p value ≤ 0,05) Ha is accepted, meaning there is a relationship with Attitudes towards Personal Hygiene. The results of the Chi Square Statistical test showed that the p value was ≥ 0,05, namely 0,113, so Ha was rejected, meaning there was no relationship between behavior and Personal Hygiene. Conclusion: There is no relationship between knowledge and Personal Hygiene so Ha is rejected These result show that there is no significant relationship between knowledge and Personal Hygiene, There is a relationship between attitudes towards Personal Hygiene so that Ha was accepted These result can be concluded that there is a relationship between attitudes towards Personal Hygiene, There is no relationship between behavior towards Personal Hygiene so that Ha was rejected these results show that there is no significant relationship between behavior towards Personal Hygiene.